Consensus methods: characteristics and guidelines for use - Fink, A; Kosecoff, J; Chassin, M; Brook, R H (American journal of public health (1971), 1984)
Consensus methods are being used increasingly to solve problems in medicine and health. Their main purpose is to define levels of agreement on controversial subjects. Advocates suggest that, when properly employed, consensus strategies can create structured environments in which experts are given the best available information, allowing their solutions to problems to be more justifiable and credible than otherwise. This paper surveys the characteristics of several major methods (Delphi, Nominal Group, and models developed by the National Institutes of Health and Glaser) and provides guidelines for those who want to use the techniques. Among the concerns these guidelines address are selecting problems, choosing members for consensus panels, specifying acceptable levels of agreement, properly using empirical data, obtaining professional and political support, and disseminating results.